A novel hybrid treatment for pharmaceutical wastewater implying electroflocculation, catalytic ozonation with Ni-Co Zeolite 5A° catalyst followed by ceramic membrane filtration. (February 2023) - Masood, Zafar; Ikhlaq, Amir; Rizvi, Osama Shaheen; Aziz, Hafiz Abdul; Kazmi, Mohsin; Qi, Fei
Abstract: The removal of veterinary antibiotics in pharmaceutical wastewaters become more challenging with modern-day technologies due to their persistent nature. In a sequence, the release of veterinary antibiotics containing wastewater such as Enrofloxacin (EFC) and Tylosin Tartrate (TT) in water bodies has increased the chance for bacteria to attain the antibiotic resistance genes and also moved to others via horizontal gene movement. As a result, the microbes become more resistant even to conventional antibiotics due to the growth of antibiotic resistance genes in microbes. Consequently, conventional treatment technologies just partially remove the pharmaceuticals from the wastewater and are not fully effective because they are not premeditated to remove antibiotics drugs. This alarming situation seriously threatens human well-being and aquatic life. Therefore, it is indeed important to develop an economical advanced oxidation treatment method for the efficacious treatment of pharmaceutical wastewater (PhWW). In the current study, a novel approach was adopted by implying Electroflocculation (EF), Catalytic ozonation (CO) in combination with novel catalyst Ni-Co-Zeolite 5A° followed by Ceramic membrane filtration (CMF). For the first time, in the current investigation, the studied hybrid process (EF + CO–CMF) using Zeolite 5A° coated with double metal salts of Nickel and Cobalt was applied as a catalyst in ozonation (O3 ) for the treatment of PhWW. Moreover, the removal of COD, BOD5, and turbidity was also studied and compared with national and international effluent quantity discharge standards. The obtained results exhibited that the combined EF + CO process has achieved removal efficiencies of 33 %, 93 %, 78 %, 45 %, and 60 % for EFC, TT, COD, BOD5, and turbidity respectively. Furthermore, the integration of CMF after EF + CO has enhanced the removal of pollutants up to the mark. It was revealed that the novel combined treatment method EF + Ni-Co Zeolite 5A°/O3 –CMF has removed the EFC, TT, COD, BOD5, and turbidity of 97 %, 98 %, 90 %, 86 %, and 93 % respectively at optimum conditions (pH = 7.1 ± 0.2; treatment time = 30 min; EF voltage = 10 V; catalyst dose = 10 g/L; O3 = 1.1 mg/min). Additionally, it was observed that biodegradability (BOD5 /COD ratios) enhanced from 0.48 to 0.60, and become easily biodegradable for further treatment. Henceforth, EF + Ni-Co Zeolite 5A°/O3 –CMF treated wastewater has also complied with the Punjab Environmental Quality Standards (PEQS). Therefore, this novel hybrid treatment process may efficaciously apply at an industrial scale for the treatment of veterinary antibiotics containing PhWW. Graphical abstract: Unlabelled Image Highlights: Pharmaceutical wastewater was treated with a combined treatment method. Novel catalyst Ni-Co-Zeolite 5A° was prepared and applied in ozonation. EF + Ni-Co-Zeolite 5A°/O3 –CMF showed the highest removal of pollutants. Enrofloxacin and tylosin tartrate of 97 % and 98 % were removed respectively. Biodegradability (BOD5 /COD ratios) was improved from 0.48 to 0.60.